2011
DOI: 10.1007/s10924-011-0400-7
|View full text |Cite
|
Sign up to set email alerts
|

Film-Forming Starch Composites for Agricultural Applications

Abstract: Biodegradable polymer composites were prepared from starch, crude glycerol, rapeseed cake and urea. The uniform films of the composites were prepared by casting technique. Mechanical properties and solubility in water of the films were studied. Increase of the content of rapeseed cake in the composites lead to the decrease of tensile strength and to the increase of elongation at break. The solubility of the composites in water increased with the increase of the content of rapeseed cake and urea. The changes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Besides applications as films, some research showed that they could be used to construct disposable plant pots. By adjusting the ratio of its component(starch, glycerol, rapeseed cake, and urea), the pH of the plant pots can be raised to reduce some danger to plants [45].…”
Section: Current Study On Agricultural Applicationsmentioning
confidence: 99%
“…Besides applications as films, some research showed that they could be used to construct disposable plant pots. By adjusting the ratio of its component(starch, glycerol, rapeseed cake, and urea), the pH of the plant pots can be raised to reduce some danger to plants [45].…”
Section: Current Study On Agricultural Applicationsmentioning
confidence: 99%
“…Film casting has been widely used for starch-based polymer film processing for food, conventional plastic replacing material and agricultural use (Bourtoom and Chinnan, 2008, Grazuleviciene et al, 2012, Koch et al, 2010, Lu et al, 2012, Wu and Zhang, 2001, Jimenez et al, 2012a. The general process includes the preparation of a suspension mixture followed by gelatinisation, casting and drying.…”
Section: Tps Processingmentioning
confidence: 99%